2022
DOI: 10.1111/jora.12751
|View full text |Cite
|
Sign up to set email alerts
|

Systems of Oppression: The Impact of Discrimination on Latinx Immigrant Adolescents’ Well‐Being and Development

Abstract: With over 400 harmful immigration policy changes in the past 4 years, Latinx adolescents and families nationwide are developing within a context of extreme anti-immigrant sentiment (Dismantling and reconstructing the U.S. immigration system: A catalog of changes under the Trump presidency, Migration Policy Institute, 2020). This paper introduces the Multitiered Model of Oppression and Discrimination (MMOD), a conceptual model for understanding the impacts of multiple levels of discrimination on the well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 106 publications
(130 reference statements)
2
22
0
Order By: Relevance
“…Findings in this issue support the MMOD model (Torres et al, 2022) 2022) found that immigrant and undocumented adolescents reported exclusion by peers and school staff in virtual (e.g., social media and virtual video games) and nonvirtual settings. Undocumented students described being told that they were taking "someone else's space" in school because places like schools are connected to governments, and thus, they should only attend schools within governments in which they were citizens (L opez Hern andez et al, 2022).…”
Section: Overarching Themes Of the Special Issuesupporting
confidence: 65%
See 4 more Smart Citations
“…Findings in this issue support the MMOD model (Torres et al, 2022) 2022) found that immigrant and undocumented adolescents reported exclusion by peers and school staff in virtual (e.g., social media and virtual video games) and nonvirtual settings. Undocumented students described being told that they were taking "someone else's space" in school because places like schools are connected to governments, and thus, they should only attend schools within governments in which they were citizens (L opez Hern andez et al, 2022).…”
Section: Overarching Themes Of the Special Issuesupporting
confidence: 65%
“…Qualitative approaches play a valuable role in generating knowledge about systems of oppression. Studies in this special issue center on the voices of BIPOC youth and illustrate their meaning‐making about systems of oppression, the different contexts and processes by which racial and other forms of oppression are exacted on particular groups of youth, and developmental patterns in recognizing and understanding life experiences that are oppressive (Harris & Kruger, 2022; López Hernández, 2022; Pasco et al., 2022; Sánchez et al., 2022; Torres et al., 2022). This work illustrates the everyday spaces where racialized forms of oppression occur—such as schools, peer groups, social media, restaurants, and public transit—as well as institutions such as police and exclusionary policies, such as anti‐immigration laws.…”
Section: Research Designs and Methods That Advance Understanding Of S...mentioning
confidence: 99%
See 3 more Smart Citations